Effect of nonsurgical periodontal treatment on clinical periodontal variables and salivary resistin levels in obese Asians - Akram, Z.; Baharuddin, N.A.; Vaithilingam, R.D.; Rahim, Z.H.A.; Chinna, K.; Krishna, V.G.; Saub, R.; Safii, S.H. (2017)
This study investigated changes in periodontal outcomes after nonsurgical periodontal treatment (NSPT) and evaluated associations of change in salivary resistin level with periodontal outcomes in obese Malaysians with chronic periodontitis. Sixty-two obese adults with chronic periodontitis were randomly divided into a test group (n = 31), which received NSPT, and a control group (n = 31), which received no treatment. Plaque score (PS), gingival bleeding index (GBI), probing pocket depth (PPD), and clinical attachment loss (CAL) were measured at baseline and at 6 and 12 weeks after NSPT. Salivary resistin levels were evaluated by using an enzyme-linked immunosorbent assay. PS was significantly lower in patients who received NSPT than in the control group at 6 and 12 weeks (P < 0.05). In the NSPT group the percentages of sites with shallow and moderate pockets decreased significantly, but there was no significant change in deep pockets. Resistin levels significantly decreased after NSPT (P < 0.05). Change in salivary resistin level was not significantly associated with periodontal outcomes. In obese Malaysians, NSPT significantly improved PS and GBI, and improved PPD and CAL for shallow and moderately deep pockets but not for deep pockets. Salivary resistin level was not associated with improvement in either periodontal variable.